PENTINGNYA PENANAMAN ADAB DAN ETIKA DI KALANGAN REMAJA - Budiharti; Aulia Tsania; Putri Rahmawati; Salsabila Octaviasari; Deri Anggraini; Kurniawati, Wahyu (Media Inovasi Pendidikan dan Publikasi, 2024)
Abstract: Juvenile delinquency is any act committed by adolescents that violates the rules that apply in society. The development of adolescence is more vulnerable to new changes, such as the changes that occur during this period. The purpose of this research is the cultivation of manners and ethics in adolescents along with solutions to overcome the deviation of manners and ethics in adolescents. The research method uses counseling methods based on case study studies. With the results that in the era of society 5.0 there is a decline in ethical values in adolescents such as a lack of caring attitude, irresponsibility with the social environment, family and parents and tends to follow the current fashion. Through the cultivation of manners and ethics, this is one of the solutions that can be done to prevent, reduce, and break the cycle of juvenile delinquency